STRATEGIC PRIORITIES OF SPATIAL AND ECONOMIC DEVELOPMENT OF UKRAINIAN REGIONS - Rodchenko , V. B.; Prus , Yu. I. (The actual problems of regional economy development, 2020)
The purpose of the article is to develop an approach to the diagnosis of strategic priorities of spatial and economic development of Ukrainian regions. Analyzing, systematizing and generalizing the scientific works of many scholars, a model of sustainable development strategy of region is proposed. After analyzing the distribution of funding for Action Plans of Development Strategies of Ukrainian regions for years 2021-2023 by the envisaged projects, the study highlighted the priorities of focusing strategies for the development of Ukrainian regions. Most regions of Ukraine are characterized by strategies of exclusive and selective focusing; a balanced distribution of funding between the components of spatial and economic development has not been identified in any region. Based on the data on the distribution of funding sources for Action Plans of Development Strategies of Ukrainian regions for years 2021-2023 (state budget, local budget, other funds), the reactive and proactive models of spatial and economic development policy implementation are specified. The first of them provides for the improvement of conditions for spatial and economic development in the vast majority through government subventions and targeted government programs, the second – aimed at attracting funds from domestic and foreign investors and the implementation of development projects. The article also assesses the qualitative parameters of Action Plans of Development Strategies of Ukrainian regions: indices of their aggressiveness and development are offered and calculated. The tools proposed by the authors to highlight the strategic priorities of spatial and economic development of the regions can be used by authorities at various levels in the preparation of program and strategic documents for both short-term and long-term perspective.